Heat transfer comparison between the one-directional and the bi-directional flows across heated tube banks with staggered configuration - Mohd Sa'at, Fatimah Al-Zahrah; Hasbullah, Nurjannah; Shikh Anuar, Fadhilah; Johari, Dahlia (2023)
Development of technology requires better heat transfer knowledge that covers variety of flow conditions. This paper reported experimental works that show the difference in fluid dynamics behavior between the one-directional flow and the bi-directional flow condition that led toward different heat transfer performance when the fluid flows over heated tube banks with staggered arrangement. The bi-directional flow was investigated based on a thermoacoustic condition with standing wave environment. Results revealed that the heat transfer of the investigated bi-directional flow is lower than that of the one-directional flow under similar Reynolds condition. This happens due to the different fluid dynamics exhibited by the two tested conditions.